Factores determinantes de la eficiencia en la industria manufacturera de las economías del APEC, 2000-2022. Un estudio a través del DEA radial y no radial con variables ambientales - Ruiz Reyes, Erika Andrea (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
This research analyzes manufacturing industry efficiency in 17 of 21 APEC economies from 2000 to 2022, divided into developed economies (Australia, Canada, Hong Kong, Japan, New Zealand, Republic of Korea, Singapore, and United States of America) and developing economies (China, Indonesia, Malaysia, Mexico, Peru, Philippines, Russia, Thailand, and Vietnam).Radial efficiency measures are implemented with the basic output-oriented VRS model and non-radial efficiency measures with the Slack-Based Model (SBM) with VRS and also output-oriented, incorporating an analysis one with enviromental variables and the other without environmental variables. The study uses as inputs the number of workers and investment, while as outputs consider the added value (good output) and CO2 emissions (bad output). The results reveal distinctive patterns between developed and developing economies. Developed economies such as Hong Kong, South Korea, New Zealand, and Singapore maintained levels of efficiency in the manufacturing industry close to 1.0000 in mosto f the periods, analysed, demonstrating outstanding resource management. In contrast, developing economies like Mexico, Indonesia, and Vietnam showed inefficiencies.Radial measures tended to show higher efficiencies than non-radial ones, although the latter proved more rigorous for evaluating environmental efficiency.

Esta investigación analiza la eficiencia de la industria manufacturera en 17 de las 21 economías del APEC durante el período 2000-2022, divididas en economías desarrolladas (Australia, Canadá, Hong Kong, Japón, Nueva Zelanda, República de Corea, Singapur y Estados Unidos de América) y en desarrollo (China, Indonesia, Malasia, México, Perú, Filipinas, Rusia, Tailandia y Vietnam). Se instrumentan medidas de eficiencia radial con el modelo básico orientado a outputs con VRS y medidas de eficiencia no radial con el modelo Slacks-Based Measure (SBM) con VRS y orientación al output, incorporando un análisis con variables ambientales y otro sin variables ambientales. El estudio emplea como inputs el número de trabajadores y la inversión, mientras que cómo outputs consideran el valor agregado (good output) y las emisiones de CO2 (bad output). Los resultados revelan patrones distintivos entre las economías desarrolladas y en desarrollo. Las economías desarrolladas como Hong Kong, Corea del Sur, Nueva Zelanda y Singapur mantuvieron niveles de eficiencia en la industria manufacturera cercanos a 1.0000 en la mayoría de los períodos analizados, demostrando una gestión sobresaliente de recursos. En contraste, las economías en desarrollo como México, Indonesia y Vietnam mostraron ineficiencias. Las medidas radiales tendieron a mostrar eficiencias más altas que las no radiales, estas últimas resultaron más rigurosas para evaluar la eficiencia ambiental.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2025-1209; Eficiencia manufacturera; APEC; Emisiones CO2; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19427